Both fearful and happy expressions interact with gaze direction by 200 ms SOA to speed attention orienting. Issue 4 (21st April 2018) - McCrackin, Sarah D.; Itier, Roxane J.
ABSTRACT: Attention orienting towards a gazed-at location is fundamental to social attention. Whether gaze cues can interact with emotional expressions other than those signalling environmental threat to modulate this gaze cueing, and whether this integration changes over time, remains unclear. With four experiments we demonstrate that, when perceived motion inherent to dynamic displays is controlled for, gaze cueing is enhanced by both fearful and happy faces compared to neutral faces. This enhancement is seen with stimulus-onset asynchronies ranging from 200–700 ms. Thus, gaze cueing can be reliably modulated by positive expressions, albeit to a smaller degree than fearful ones, and this gaze–emotion integration impacts behaviour as early as 200 ms post-cue onset.